The (un)suitability of modern liquid crystal displays (LCDs) for vision research - Ghodrati, Masoud; Morris, Adam P.; Price, Nicholas Seow Chiang (Frontiers in Psychology, 2015)
Psychophysical and physiological studies of vision have traditionally used cathode ray tube (CRT) monitors to present stimuli. These monitors are no longer easily available, and liquid crystal display (LCD) technology is continually improving; therefore, we characterised a number of LCD monitors to determine if newer models are suitable replacements for CRTs in the laboratory. We compared the spatial and temporal characteristics of a CRT with five LCDs, including monitors designed with vision science in mind (ViewPixx and Display++), “prosumer” gaming monitors, and a consumer-grade LCD. All monitors had sufficient contrast, luminance range and reliability to support basic vision experiments with static images. However, the luminance of all LCDs depended strongly on viewing angle, which in combination with the poor spatial uniformity of all monitors except the VPixx, caused up to 80% drops in effective luminance in the periphery during central fixation. Further, all monitors showed significant spatial dependence, as the luminance of one area was modulated by the luminance of other areas. These spatial imperfections are most pronounced for experiments that use large or peripheral visual stimuli. In the temporal domain, the gaming LCDs were unable to generate reliable luminance patterns; one was unable to reach the requested luminance within a single frame whereas in the other the luminance of one frame affected the luminance of the next frame. The VPixx and Display++ were less affected by these problems, and had good temporal properties provided stimuli were presented for 2 or more frames. Of the consumer-grade and gaming displays tested, and if problems with spatial uniformity are taken into account, the Eizo FG2421 is the most suitable alternative to CRTs. The specialized ViewPixx performed best among all the tested LCDs, followed closely by the Display++; both are good replacements for a CRT, provided their spatial imperfections are considered.